INNOVATIVE COMPETENCE AS A COMPONENT OF THE PROFESSIONAL ACTIVITY OF A MODERN TEACHER - Nadiia О. Vientseva; Olena V. Karapetrova (Alfred Nobel University Publisher, 2022)
The article is devoted to the issues of innovative competence as a professional activity of a modern teacher. The concept of «competence» is analyzed, which in modern pedagogical science is defined as an integrative property of the individual resulting from the synthesis of basic training, practical and personal experience. The opinions of scientists on the definition of «innovative competence» are summarized, which implies the presence of innovative perception of the subject: the perception of their own innovations and innovations or discoveries in general, the ability to see new elements in a relatively stable situation and propose a fundamentally new solution. The innovative competence of a teacher is considered as a component of general professional and pedagogical competence, the content of which is determined by the peculiarities of innovative activity, its social significance, creative nature and focus on continuous creation of new, personal and professional potential of teachers. The most characteristic features of innovative competence of the teacher are distinguished, which include: 1) personal orientation of the specialist to learn something new, the willingness to change the ways of professional activity; 2) the subjectivity of goal setting, goal realization and self-realization; 3) the clarity of professional position, awareness of the social significance of innovations, inclusion in social creativity; 4) the compliance of the composition of competence with the structure of innovation activity; 5) the effectiveness of ways to implement a system of knowledge, skills, abilities at all stages of the innovation process; 6) the ability to be creative in solving professional problems; 7) the integrity of the whole set of competencies in the innovative competence of the specialist as a system entity; 8) the high level of professionalism of the specialist, based on the understanding and self-improvement of their professional experience. The factors of formation of innovative competence of a teacher are determined, which include: readiness of teachers for innovation; availability of resources for the implementation of innovations; critical thinking; imagination; motivational and value attitude to professional activity; the ability to reflect. It is proved that the formation and development of innovative competence of teachers of educational institutions is holistic and successful, first of all, under the appropriate level of internal innovation environment, which is determined by the mission, goals and strategies of educational institution, creative socio-psychological climate, effective management systems and information and methodological support of innovations, effective connections and ways of communication both within the educational institution and with other educational institutions.